UTILIZING DUOLINGO APPLICATION TO ENHANCE YOUNG LEARNERS’ VOCABULARY MASTERY - Yulia Inayatul Ulfa; Wiyaka; Entika Fani Prastikawati (Universitas PGRI Palembang, 2025)
This study aims to investigate the effectiveness of the Duolingo application in improving vocabulary mastery and to identify student perceptions of its use in junior high school. Using a one-group pre-test and post-test design, a pre-experimental approach was used with 34 eighth-grade students from SMP N 6 Semarang. Data were collected through a written vocabulary test and a closed-ended questionnaire, and analyzed using SPSS 26 software. The main findings demonstrated a notable rise in vocabulary scores, with the mean score rising from 62.79 to 86.24, supported by a t-test result (t = 7.618, p < 0.05). Most students responded positively, citing Duolingo's user-friendly interface, engaging content, and motivating features. This study can be applied in English language teaching, especially at the junior high school level, and also contributes to mobile-assisted language learning research. The novelty of this study lies in its focus on integrating gamified mobile applications into vocabulary instruction in English classrooms, providing new insight into learner engagement and digital tool effectiveness.